(untitled) (Research, Society and Development, 2026)
Objective: To compare in vitro the antibacterial activity of an active oxygen-based mouthwash (blue®m) and 0.12% chlorhexidine against Porphyromonas gingivalis ATCC 33277 by evaluating the diameter of the inhibition halo at different time intervals. Materials and methods: An in vitro experimental study with a 2×3 factorial design was conducted. The agar diffusion method was applied using supplemented Mueller–Hinton agar, with incubation under anaerobic conditions. Antibacterial activity was assessed at 4, 8, and 12 hours. Statistical analysis included descriptive statistics and two-way analysis of variance (ANOVA), followed by Tukey’s post hoc test, adopting a significance level of p < 0.05. Results: Both mouthwashes exhibited antibacterial activity against Porphyromonas gingivalis at all evaluated time points. No statistically significant differences were observed between the groups at 4 and 8 hours. However, at 12 hours, 0.12% chlorhexidine showed a significantly greater inhibitory effect compared to the active oxygen mouthwash (p = 0.033). Conclusion: The active oxygen-based mouthwash demonstrated antibacterial activity comparable to chlorhexidine during the initial evaluation periods; however, chlorhexidine showed greater persistence of the antimicrobial effect. These findings support the potential use of active oxygen as an adjunctive agent for the initial control of anaerobic periodontal pathogens.